Development and Innovation of Curriculum in Foreign Language - Lelakova, Eva (Advances in Social Sciences Research Journal, 2015)
The primary aim of the Faculty of Humanities of the University of Žilina in Žilina is providing education of a very high quality. Its realization is evaluated not only by the Accreditation commission but also by the Slovak government advisory body which monitors, reviews and independently evaluates the quality of educational, research, development, artistic and other activities of Slovak universities. The evaluation of Academic ranking and rating agency (ARRA) is based on publicly available and verifiable data concerning the quality of education and research of individual faculties in Slovakia. It is often a decisive criterion in the selection of the university where the students will be studying. The Faculty of Humanities was ranked first in the group of philosophical faculties in the 2012 ARRA evaluation in Slovakia and its aim has become a continuous, high-quality training of students in order to improve their labour market success. To reach the mentioned aim the faculty participates in various projects concentrating on the development and innovation of curriculum with emphasis on the needs of the labour market and knowledge society. As intercultural communication is nowadays one of the key priorities and important pre-conditions for the processes of globalization, our project team has decided to prepare accreditation documents for the study programme Intercultural communication focusing on comparison of socio-cultural dimensions of English speaking countries with the national peculiarities of Slovakia.